'The world needs more Canada': Are there lessons for European progressives in the Liberals' comeback?. Issue 4 (March 2017) - Chwalisz, Claudia
Abstract : As centre‐left parties falter across Europe, Claudia Chwalisz wonders whether progressives can find the roots of a resurgence in Justin Trudeau's victory. Or is there nothing for them to learn from this uniquely Canadian tale?